1995
DOI: 10.1136/thx.50.9.941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary sodium on airways responsiveness and its importance in the epidemiology of asthma: an evaluation in three areas of northern England.

Abstract: Conclusions -If airways responsiveness is related to dietary sodium the relationship is not likely to be strong. (Thorax 1995;50:941-947)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…It has been suggested that dietary sodium might affect airway responsiveness (and so might exert a confounding influence on epidemiologic investigations of asthma), but in the present study urinary sodium excretion showed no differences between workers and school leaver control subjects, nor across the exposure subgroups, and it was not related to PD 20 measurements (29). It was not considered further in the investigation.…”
Section: Clinical Surveycontrasting
confidence: 76%
“…It has been suggested that dietary sodium might affect airway responsiveness (and so might exert a confounding influence on epidemiologic investigations of asthma), but in the present study urinary sodium excretion showed no differences between workers and school leaver control subjects, nor across the exposure subgroups, and it was not related to PD 20 measurements (29). It was not considered further in the investigation.…”
Section: Clinical Surveycontrasting
confidence: 76%
“…123 Three other observational studies on relatively large groups of normal men and boys did not reveal a relation between urinary sodium excretion and bronchial reactivity to methacholine. [124][125][126][127] Conclusion: The level of salt intake may be injurious to male patients with asthma. There is no evidence that salt intake effects airway responsiveness in normal subjects.…”
Section: Asthmamentioning
confidence: 99%
“…A subsequent study examining dietary salt intake and bronchial reactivity in men revealed a positive correlation between airway reactivity and 24-h urine sodium excretion. In contrast to the aforementioned studies, a number of large cohort studies have failed to observe any associations between 24-h urinary sodium excretion and airway reactivity (11,21,59,66). Two large cohort studies by Britton et al (11) and Devereux et al (21) found no association between airway hyperresponsiveness and sodium excretion.…”
mentioning
confidence: 96%
“…In contrast to the aforementioned studies, a number of large cohort studies have failed to observe any associations between 24-h urinary sodium excretion and airway reactivity (11,21,59,66). Two large cohort studies by Britton et al (11) and Devereux et al (21) found no association between airway hyperresponsiveness and sodium excretion. Furthermore, Sparrow et al (59) observed an association between airway reactivity and urinary potassium, but not sodium secretion.…”
mentioning
confidence: 96%